A method for preparing ultra-high molecular weight polyethylene by copolymerizing ethylene and alpha-olefin

By copolymerizing ethylene with α-olefin and using titanium metal catalysts, the problem of difficulty in maintaining the molecular weight of ultra-high molecular weight polyethylene in the prior art is solved, and the efficient preparation of ultra-high molecular weight polyethylene is achieved, which improves its performance and market competitiveness.

CN116589616BActive Publication Date: 2025-03-18QINGDAO UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310657417.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2025-03-18
Estimated Expiration
2043-06-05

AI Technical Summary

Technical Problem

The prior art is difficult to effectively maintain the molecular weight of ultra-high molecular weight polyethylene, affecting its performance.

Method used

By copolymerizing ethylene with α-olefin and using a specific titanium metal catalyst, chain transfer and β-H elimination termination reaction are inhibited, thereby increasing the molecular weight of the polymer.

Benefits of technology

It has achieved efficient preparation of ultra-high molecular weight polyethylene with a molecular weight of more than 5 million, which has the advantages of simplicity, low cost and narrow molecular weight distribution of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116589616B_ABST
    Figure CN116589616B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing ultra-high molecular weight polyethylene by copolymerizing ethylene and α-olefin. The present invention introduces α-olefin as a comonomer. After the insertion of α-olefin, the energy barrier of β-H elimination / chain transfer reaction is higher, the chain transfer and β-H elimination termination reaction are inhibited, and the molecular weight of the polymer is greatly increased. The method for preparing ultra-high molecular weight polyethylene reported in the present invention has the advantages of being simple and easy to operate, low cost, and narrow product molecular weight distribution, and the activity is as high as 8.1×10 7 g·mol ‑1 (Ti) h ‑1 , preparing ultra-high molecular weight polyethylene with a molecular weight exceeding 5 million. Therefore, the present invention has original innovation and can enhance the competitiveness of my country's polyolefin polymer material technology market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for synthesizing ultra-high molecular weight polyethylene. Background Art

[0002] Among general plastics, polyethylene has the largest output and the widest application. Ultra-high molecular weight polyethylene (UHMWPE) is a high-density PE with excellent performance. It is an important thermoplastic engineering plastic. It was first successfully developed by the United Chemical Company of the United States in 1957 using Ziegler catalyst. It is a linear polymer with a molecular weight of 1 to 5 million, a crystallinity of 65% to 85%, and a density of 0.92 to 0.96 g / cm 3 . UHMWPE has the same molecular structure as ordinary PE, and the main chain segments are all (CH2-CH2). It is a typical representative of high-performance polyolefin materials. Compared with ordinary polyethylene, it has many excellent properties, such as better impact resistance, wear resistance, chemical corrosion resistance, self-lubrication, cold resistance, stress cracking resistance, and anti-adhesion. In recent years, UHMWPE processing and modification technologies have been increasingly expanded and optimized, forming a variety of UHMWPE products, which play an important role in various fields of the national economy and are called "strange plastics". The main products include fibers, films, pipes, plates, rods, porous materials and special-shaped materials, which are widely used in aerospace, national defense and military industry, marine engineering, rail transportation, municipal construction, petrochemicals, mining, metallurgy, electricity, new energy materials and other fields (Angew. Chem. Int. Ed., 2021, 60, 4018). .

[0003] The many excellent properties of UHMWPE are closely related to its molecular weight. In order to obtain high-performance UHMWPE, it is necessary to maintain its ultra-high molecular weight as much as possible (Angew. Chem. Int. Ed., 2022, 61, e202207363). The catalyst is the core factor affecting the molecular weight of UHMWPE. The global market of UHMWPE is growing at a rate of 5%. As a new type of engineering thermoplastic, the application of UHMWPE has infinite prospects. It is very important and imperative to carry out the research and development of related catalysts. The preparation of UHMWPE belongs to a branch of polyolefin synthesis. The development of catalysts has also gone through several types. According to different development stages, it can be divided into three categories: Ziegler-Natta (ZN) catalysts, metallocene catalysts and non-transition metallocene catalysts. Non-transition metallocene catalysts do not contain cyclopentadienyl groups. The ligands are organic groups containing coordination atoms such as oxygen, nitrogen, sulfur and phosphorus. The central metal includes all transition metal elements. Compared with metallocene, non-metallocene catalysts not only maintain all the advantages of metallocene catalysts, but also have their own unique advantages: ① The synthesis of non-metallocene ligands is simpler and the cost is relatively low, and its price is only 1 / 10 of that of metallocene catalysts; ② The skeleton is easy to modify, the ligand is flexible, and it is easy to modify the catalyst in terms of steric effect and electronic effect, which can realize the free design of molecules; ③ It has stronger tolerance to heteroatom groups, has active polymerization characteristics and good polar monomer copolymerization ability, and can customize the properties of polymers. Therefore, it is of great significance and imperative to develop non-metallocene early transition metal catalysts that can prepare ultra-high molecular weight polyethylene.

[0004] The present invention reports a method for preparing ultra-high molecular weight polyethylene by copolymerizing ethylene and α-olefin. The present invention introduces α-olefin as a comonomer. After the insertion of α-olefin, the energy barrier of β-H elimination / chain transfer reaction is higher, which inhibits chain transfer and β-H elimination termination reaction and greatly increases the molecular weight of the polymer. The method for preparing ultra-high molecular weight polyethylene reported in the present invention has the advantages of being simple and easy to operate, low cost, and narrow product molecular weight distribution. The activity is as high as 8.1×10 7 g·mol -1 (Ti) h -1 , preparing ultra-high molecular weight polyethylene with a molecular weight exceeding 5 million. Therefore, the present invention has original innovation and can enhance the competitiveness of my country's polyolefin polymer material technology market. Summary of the invention

[0005] The purpose of the present invention is to provide a method for synthesizing ultra-high molecular weight polyethylene.

[0006] In the above synthesis method, the catalyst used is a titanium metal catalyst represented by formula (I):

[0007]

[0008] The preparation method of the above-mentioned catalyst, as shown in formula (II), comprises the following steps:

[0009]

[0010] 4.5 molar equivalents of potassium hydroxide (15.12 g, 270 mmol) and MeI (18.0 mL, 270 mmol) were added to 1 molar equivalent of N-substituted phenyl-2-nitroaniline, and the mixture was stirred at room temperature for 12 hours. After the reaction, the mixture was quenched with 500 mL of deionized water, extracted with 3×500 mL of ethyl acetate, and the organic phase was dehydrated and the solvent was removed under reduced pressure to obtain N-methyl-N-substituted phenyl-2-nitroaniline; SnCl2 (91 g, 0.48 mol), hydrochloric acid (37 wt%, 100 mL) and anhydrous ethanol (80 mL) were added to carry out reduction reaction for 12 hours, and then 2 M sodium hydroxide was used to reduce the mixture. The reaction mixture is alkalized to pH 8, extracted with ethyl acetate (3×100 mL), the organic phase is dried to remove the solvent, and then purified by column chromatography (eluent: DCM / PE=1 / 1, v / v) to obtain N-methyl-N-substituted phenyl-o-phenylenediamine; further reacted with 1 molar equivalent of salicylaldehyde to obtain 1-L or 2-L or 3-L or 4-L ligand; the ligand and 1 molar equivalent of NaH are stirred in toluene at room temperature overnight, 1 molar equivalent of TiCl4 is added, and stirring is continued at 110°C for 72 hours. After returning to room temperature, it is first filtered, and after the filtrate is drained of the solvent, it is washed with 5 mL of anhydrous n-hexane to obtain the titanium metal catalyst.

[0011] In the above-mentioned synthesis method of ultra-high molecular weight polyethylene, a co-catalyst is also added, and the co-catalyst is one or more of trispentafluorophenyl boron, triphenylcarbonium tetrakis(pentafluorophenyl)borate, aluminoxane, alkyl aluminum and alkyl aluminum chloride. The aluminoxane is methyl aluminumoxane, ethyl aluminumoxane or isobutyl aluminumoxane; the alkyl aluminum is trimethyl aluminum, triethyl aluminum, triisobutyl aluminum or tri-n-hexyl aluminum; the alkyl aluminum chloride is diethyl aluminum monochloride, diethyl aluminum sesquichloride or ethyl aluminum dichloride.

[0012] In the above-mentioned synthesis method of ultra-high molecular weight polyethylene, α-olefin needs to be introduced to copolymerize with ethylene to increase the molecular weight of polyethylene; the α-olefin is one or more of 1-butene, 1-hexene, and 1-octene.

[0013] In the above-mentioned synthesis method of ultra-high molecular weight polyethylene, the polymerization temperature is 0-180° C., the polymerization pressure is 0.1-5 MPa, and the polymerization solvent is one or more of toluene, hexane, and heptane.

[0014] The present invention provides a method for preparing ultra-high molecular weight polyethylene by copolymerizing ethylene and α-olefin. The present invention introduces α-olefin as a comonomer. After the insertion of α-olefin, the energy barrier of β-H elimination / chain transfer reaction is higher, which inhibits chain transfer and β-H elimination termination reaction and greatly increases the molecular weight of the polymer. The method for preparing ultra-high molecular weight polyethylene reported in the present invention has the advantages of being simple and easy to operate, low cost, and narrow product molecular weight distribution. The activity is as high as 8.1×10 8 g·mol -1 (Ti) h -1 , preparing ultra-high molecular weight polyethylene with a molecular weight exceeding 5 million. Therefore, the present invention has original innovation and can enhance the competitiveness of my country's polyolefin polymer material technology market. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the crystal structure diagram of titanium metal catalyst 3-TiCl3.

[0016] Figure 2 This is the GPC chart of high-density polyethylene prepared by ethylene homopolymerization in Example 7.

[0017] Figure 3 This is the GPC chart of the ultra-high molecular weight polyethylene prepared by copolymerization of ethylene and 1-octene in Example 12. DETAILED DESCRIPTION

[0018] The present invention is further described by way of examples, but the present invention is not limited thereto. The examples of the present invention can enable those skilled in the art to understand the present invention more comprehensively.

[0019] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0020] In the present invention, 2,6-iPr-C6H3-NMe-C6H4-NO2, 2,6-Me-C6H3-NMe-C6H4-NO2, C6H5-NMe-C6H4-NO2, and 2,6-F-C6H3-NMe-C6H4-NO2 are synthesized according to the method reported in the literature J. Org. Chem, 2013, 78(8): 3532-3540.

[0021] The present invention is described below with reference to specific embodiments.

[0022] Example 1. Preparation of Titanium Metal Catalyst 1-TiCl3

[0023] 4.5 molar equivalents of potassium hydroxide (15.12 g, 270 mmol) and MeI (18.0 mL, 270 mmol) were added to 2,6-iPr-C6H3-NH-C6H4-NO2 (17.90 g, 60 mmol), and the mixture was stirred at room temperature for 12 hours. After the reaction, the mixture was quenched with 500 mL of deionized water, extracted with 3×500 mL of ethyl acetate, and the organic phase was dehydrated and the solvent was removed under reduced pressure to obtain 2,6-iPr-C6H3-NMe-C6H4-NO2; SnCl2 (91 g, 0.48 mol, 189.62 g / mol), hydrochloric acid (100 mL) and anhydrous ethanol (80 mL) were added for reduction reaction for 12 hours, and then the reaction mixture was alkalized to pH 8 with 2 M sodium hydroxide and extracted with ethyl acetate (3×100 mL ) was extracted, the organic phase was dried to remove the solvent and then purified by column chromatography (eluent: DCM / PE=1 / 1, v / v) to obtain 2,6-iPr-C6H3-NMe-C6H4-NH2; it was further reacted with 1 molar equivalent of 3,5-di-tert-butyl salicylaldehyde to obtain NNO-tridentate ligand; under a nitrogen atmosphere, NNO-tridentate ligand containing 2,6-diisopropyl substituent (1.00 g, 2.00 mmol) and 1.1 molar equivalents of NaH were stirred in Tol at room temperature overnight, and then 1 equivalent of TiCl4 was slowly added, and reflux stirring was continued at 110°C for 72 hours. After returning to room temperature, it was filtered first, and the filtrate was drained of the solvent and washed with 5 mL of anhydrous n-hexane to obtain a red powder 1-TiCl3 (1.00 g, 1.54 mmol, yield 77%). 1 H NMR(C6D6): δ8.21(s,1H,N=CH),7.72(d,J=2.4Hz,1H,Ar-H),7.34–7.27(m,3H,Ar-H),6.97(d,J=2 .3Hz,1H,Ar-H),6.82(d,J=8.1Hz,1H,Ar-H),6.76(t,J=7.2Hz,1H,Ar-H),6.61(t,J=7.2Hz,1H,Ar -H),5.96(dd,J=8.2,0.8Hz,1H,Ar-H),4.28(s,3H,NMe),3.53(sept,J=6.8Hz,2H,CHMe2),1.61(d ,J=6.8Hz,6H,CHCH3CH3),1.57(s,9H,CMe3),1.27(s,9H,CMe3),1.11(d,J=6.8Hz,6H,CHCH3CH3). 13CNMR (400MHz, C6D6): δ166.18 (N=CH),157.97,155.06,152.35,144.70,142.02,139.05,138.38,131.70,129.53,129.33,1 28.56,124.82,123.22,121.21,114.98,112.97,55.94(NMe),35.52,34.60,31.34,29.57,28.92,25.24,24.70.Anal.Calcd for C 34 H 45 Cl3N2OTi:C,62.64;H,6.96;N,4.30.Found:C,62.70;H,6.88;N,4.35.

[0024] Example 2. Preparation of Compound 2-TiCl3

[0025] The experimental steps were the same as those in Example 1, using 2,6-Me-C6H3-NMe-C6H4-NO2 as raw material to obtain compound 2-TiCl3 as a reddish brown solid (0.950 g, 1.60 mmol, yield 80%). 1 H NMR (400MHz, C6D6): δ8.19(s,1H,N=CH),7.71(d,J=2.4Hz,1H,Ar-H),7.15–7.07(m,3H,Ar-H),6.97(d,J=2.4Hz,1H,Ar-H),6.75–6.71(m,2H,Ar-H) ,6.55(ddd,J=8.3,7.2,1.2Hz,1H,Ar-H),5.84(d,J=8.1Hz,1H,Ar-H),4.21(s,3H,NMe),2.44(s,6H,Ar-Me),1.56(s,9H,CMe3),1.27(s,9H,CMe3). 13 C NMR (400MHz, C6D6): δ165.81 (N=CH),158.26,154.70,153.14,144.75,139.72,138.36,132.08,130.16,128.64,128 .17,127.94,127.53,123.26,121.17,114.98,111.26,55.88(NMe),35.50,34.60,31.33,29.65,19.12.Anal.Calcd for C 30 H 37Cl3N2OTi:C,60.47;H,6.26;N,4.70.Found:C,60.40;H,6.21;N,4.78.

[0026] Example 3. Preparation of Compound 3-TiCl3

[0027] The experimental steps were the same as those in Example 1, and C6H5-NMe-C6H4-NO2 was used as the raw material to obtain compound 3-TiCl3 as a reddish brown solid powder (0.92 g, 1.62 mmol, yield 81%). 1 H NMR (400MHz, CDCl3): δ8.84(s,1H,N=CH),7.68(d,J=2.3Hz,1H,Ar-H),7.61–7.57(m,1H,Ar-H),7.56–7.48(m,4H,Ar-H),7.4 2–7.35(m,2H,Ar-H),7.24(s,1H,Ar-H),7.07(t,J=7.3Hz,2H,Ar-H),4.27(s,3H,NMe),1.46(s,9H,CMe3),1.34(s,9H,CMe3). 13 C NMR (101MHz, CDCl3) δ162.35 (N=CH),160.96,156.58,147.51,146.23,144.72,136.23,133.02,131.26,130.72, 129.59,128.29,127.39,126.74,125.01,122.26,117.51,55.95(NMe),35.56,34.89,31.34,29.92.Anal.Calcd forC 28 H 33 Cl3N2OTi· 1 / 2CH2Cl2:C,59.23;H,5.86;N,4.93.Found:C,59.19;H,5.81;N,4.90.

[0028] Example 4. Preparation of Compound 4-TiCl3

[0029] The experimental steps were the same as those in Example 1, using 2,6-F-C6H3-NMe-C6H4-NO2 as raw material to obtain compound 4-TiCl3 as a reddish brown solid (0.97 g, 1.60 mmol, yield 80%). 1H NMR (400MHz, C6D6): δ8.11 (s, 1H, N=CH), 7.67 (d, J=2.4Hz, 1H, Ar-H), 7.16–7.1 3(m,2H,Ar-H),6.94(d,J=2.4Hz,1H,Ar-H),6.85–6.81(m,1H,Ar-H),6.79–6.71 (m,1H,Ar-H),6.65–6.57(m,1H,Ar-H),6.55(t,J=8.1Hz,1H,Ar-H),6.00(dd,J =8.1,1.0Hz,1H,Ar-H),4.21(s,3H,NMe),1.55(s,9H,CMe3),1.25(s,9H,CMe3). 13 C NMR (400MHz, CDCl3): δ165.24(N=CH),158.61,152.03,150.34,145.95,138.81,137.82,132.61,132.21,130.07 ,128.77,128.53,128.12,123.38,121.48,114.76,111.58,55.92(NMe),35.41,34.83,31.41,29.62.Anal.Calcd for C 28 H 31 Cl3F2N2OTi:C,55.70;H,5.18;N,4.64.Found:C,55.75;H,5.11;N,4.60.

[0030] Example 5: 1-TiCl3 catalyzed ethylene polymerization

[0031] The autoclave was connected to a high-pressure pipeline to remove nitrogen and replace ethylene three times. 195 mL of toluene was added under ethylene atmosphere, and 3.4 mL of co-catalyst was injected with a syringe to make Al / Ti=2500, ethylene pressure 40 atm, and temperature 50°C. In a glove box, 1.2 mg (2 μmol) of 1-TiCl3 complex was added to a 10 mL sample bottle equipped with a magnetic stirrer, 5 mL of anhydrous toluene was taken with a syringe, added to the sample bottle and stirred for 5 minutes to dissolve it, and the above catalyst toluene solution was injected into the main catalyst feed tank with a syringe, and the main catalyst was pressed in with a nitrogen pressure of 45 atm (total volume 200 mL), and at 50°C, the ethylene pressure of 40 atm was maintained, and the reaction was stirred vigorously for 2 minutes. The reaction solution was neutralized with 10 mL of ethanol solution acidified with hydrochloric acid to obtain a polymer precipitate, which was washed with ethanol, and the polymer was vacuum dried overnight and weighed. Polymerization activity: 3.6×10 6 g·mol -1 (Ti) h -1. Polymer Mw = 890 kg·mol -1 , Mw / Mn=1.6.

[0032] Example 6: Ethylene polymerization catalyzed by 2-TiCl3

[0033] The polymerization process and reaction conditions were the same as in Example 5, and the catalyst used was 2-TiCl3. Polymerization activity: 62×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 750 kg·mol -1 , Mw / Mn=1.7.

[0034] Example 7: Ethylene polymerization catalyzed by 3-TiCl3

[0035] The polymerization process and reaction conditions were the same as in Example 5, and the catalyst used was 3-TiCl3. Polymerization activity: 84×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 680 kg·mol -1 , Mw / Mn=1.7.

[0036] Example 8: Ethylene polymerization catalyzed by 4-TiCl3

[0037] The polymerization process and reaction conditions were the same as in Example 5, and the catalyst used was 4-TiCl3. Polymerization activity: 12.0×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 850 kg·mol -1 , Mw / Mn=1.6.

[0038] Example 10: Copolymerization of ethylene and 1-octene catalyzed by 1-TiCl3

[0039] The autoclave was connected to a high-pressure pipeline to remove nitrogen and replace ethylene three times. 170 g of toluene was added under ethylene atmosphere, 120 g of 1-octene was injected with a syringe and 3.4 mL of a co-catalyst, so that Al / Ti=2500, ethylene pressure was 40 atm, and temperature was 120°C. In a glove box, 1.2 mg (2 μmol) of 1-TiCl3 complex was added to a 10 mL sample bottle equipped with a magnetic stirrer, 5 mL of anhydrous toluene was taken with a syringe, added to the sample bottle and stirred for 5 minutes to dissolve it, the catalyst toluene solution was injected into the main catalyst feed tank with a syringe, and the main catalyst was pressed in with a nitrogen pressure of 45 atm, at 120°C, maintaining an ethylene pressure of 40 atm, and vigorously stirred for 2 minutes. The reaction solution was neutralized with 10 mL of ethanol solution acidified with hydrochloric acid to obtain a polymer precipitate, which was washed with ethanol, and the polymer was vacuum dried overnight and weighed. Polymerization activity: 2.8×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 5300 kg·mol -1 , Mw / Mn=1.5.

[0040] Example 11: Copolymerization of ethylene and 1-octene catalyzed by 2-TiCl3

[0041] The polymerization process and reaction conditions were the same as in Example 10, and the catalyst used was 2-TiCl3. Polymerization activity: 12.0×10 6 g·mol -1 (Ti) h -1 . Polymer Mw = 4200 kg·mol -1 , Mw / Mn=1.6.

[0042] Example 12: Copolymerization of ethylene and 1-octene catalyzed by 3-TiCl3

[0043] The polymerization process and reaction conditions were the same as in Example 10, and the catalyst used was 3-TiCl3. Polymerization activity: 81×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 3600 kg·mol -1 , Mw / Mn=1.4.

[0044] Example 13: Copolymerization of ethylene and 1-octene catalyzed by 4-TiCl3

[0045] The polymerization process and reaction conditions were the same as in Example 10, and the catalyst used was 4-TiCl3. Polymerization activity: 9×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 3800 kg·mol-1 , Mw / Mn=1.6.

[0046] Example 14: Copolymerization of ethylene and 1-octene catalyzed by 3-TiCl3

[0047] The polymerization process and reaction conditions were the same as in Example 12, the catalyst used was 3-TiCl3, and the polymerization time was 5 min. Polymerization activity: 58.6×10 6 g·mol -1 (Ti) h -1 . Polymer Mw = 4220 kg·mol -1 , Mw / Mn=1.4.

[0048] Example 15: Copolymerization of ethylene and 1-octene catalyzed by 3-TiCl3

[0049] The polymerization process and reaction conditions were the same as in Example 12, the catalyst used was 3-TiCl3, and the polymerization time was 10 min. The polymerization activity was 41.7×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 4860 kg·mol -1 , Mw / Mn=1.5.

[0050] Example 16: Copolymerization of ethylene and 1-octene catalyzed by 3-TiCl3

[0051] The polymerization process and reaction conditions were the same as in Example 12, the catalyst used was 3-TiCl3, and the polymerization time was 20 min. The polymerization activity was 29.6×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 5680 kg·mol -1 , Mw / Mn=1.5.

[0052] Example 17, 3-TiCl3 catalyzed copolymerization of ethylene and 1-octene

[0053] The polymerization process and reaction conditions were the same as those in Example 12, the catalyst used was 3-TiCl3, and the polymerization time was 30 min. The polymerization activity was 29.6×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 6200 kg·mol -1 , Mw / Mn=1.6.

[0054] Example 18: Copolymerization of ethylene and 1-butene catalyzed by 3-TiCl3

[0055] The polymerization process and reaction conditions were the same as those in Example 17, the α-olefin used was 1-butene, and the polymerization time was 30 min. The polymerization activity was 63.5×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 5600 kg·mol -1 , Mw / Mn=1.7.

[0056] Example 19: Copolymerization of ethylene and 1-hexene catalyzed by 3-TiCl3

[0057] The polymerization process and reaction conditions were the same as those in Example 17, the α-olefin used was 1-hexene, and the polymerization time was 30 min. The polymerization activity was 40.6×10 6 g·mol -1 (Ti) h -1 .Polymer Mw = 5900 kg·mol -1 , Mw / Mn=1.6.

Claims

1. A method for preparing ultra-high molecular weight polyethylene by copolymerizing ethylene and α-olefin, characterized in that: The synthesis method requires the use of a titanium metal catalyst as shown in formula (I), 2. The method according to claim 1, characterized in that: The synthesis method further includes adding a co-catalyst, which is one or more of tripentafluorophenyl boron, triphenylcarbonium tetrakis(pentafluorophenyl)borate, aluminoxane, alkylaluminum and alkylaluminum chloride.

3. The method according to claim 2, characterized in that: The aluminoxane is methylaluminoxane, ethylaluminoxane or isobutylaluminoxane; the alkylaluminum is trimethylaluminum, triethylaluminum, triisobutylaluminum or tri-n-hexylaluminum; and the alkylaluminum chloride is diethylaluminum monochloride, diethylaluminum sesquichloride or ethylaluminum dichloride.

4. The method according to claim 1, characterized in that: Introduce α-olefins to copolymerize with ethylene to increase the molecular weight of polyethylene.

5. The method according to claim 4, characterized in that: The α-olefin is one or more of 1-butene, 1-hexene and 1-octene.

6. The method according to claim 1, characterized in that: The polymerization temperature is 0-180° C., the polymerization pressure is 0.1-5 MPa, and the polymerization solvent is one or more of toluene, hexane, and heptane.

7. The method for preparing the catalyst according to claim 1, as shown in formula (II), comprises the following steps: 4.5 molar equivalents of potassium hydroxide and MeI were added to 1 molar equivalent of N-substituted phenyl-2-nitroaniline, and the reaction was stirred at room temperature for 12 hours. After the reaction, 500 mL of deionized water was used to quench the reaction, and 3×500 mL of ethyl acetate was used to extract the organic phase. After dehydration, the solvent was removed under reduced pressure to obtain N-methyl-N-substituted phenyl-2-nitroaniline. SnCl2, hydrochloric acid and anhydrous ethanol were added to carry out reduction reaction for 12 hours, and then the reaction mixture was alkalized to pH 8 with 2M sodium hydroxide and ethyl acetate was used. Ester extraction, the organic phase is dried to remove the solvent and then purified by column chromatography to obtain N-methyl-N-substituted phenyl-o-phenylenediamine; further reacted with 1 molar equivalent of salicylaldehyde to obtain 1-L or 2-L or 3-L or 4-L ligand; the ligand and 1 molar equivalent of NaH are stirred in toluene at room temperature overnight, 1 molar equivalent of TiCl4 is added, and stirring is continued at 110°C for 72 hours. After returning to room temperature, it is first filtered, and the filtrate is drained of the solvent and then washed with 5 mL of anhydrous n-hexane to obtain the titanium metal catalyst.

Citation Information

Patent Citations

  • Synthesis method of zirconium and hafnium metal catalyst and application of zirconium and hafnium metal catalyst in preparation of ultra-high molecular weight polyethylene

    CN113816980A

  • Process of Preparation of Catalytic Support and Supported Metallocene Catalysts for Production of Homopolymers and Copolymers of Ethylene with Alfa-Olefins, of High and Ultra High Molecular Weight and with Broad Molecular Weight Distribution in Slurry, Bulk and Gas Phase Processes and Products Thereof

    US20090163682A1